Ancient features of Ancient Ethiopic - Bausi, Alessandro (Aethiopica, 2005)
‘Ancient features’ of Ethiopic in Aksumite inscriptions and ancient MSS must be discussed with consideration of the philological aspects implied, and their distribution may hint at the coexistence of parallel scribal traditions during Aksumite and early Post-Aksumite periods; from the 14th cent. onwards ‘ancient features’ tend to become much more sporadic and one traditional standard prevails; ancient MSS which did not observe the prevalent standard may have been systematically substituted; ‘lost traditions’ may survive in few scanty relics.